CONSERVATION OF DIVERSITY OF LOCAL FRUIT AND WILD BERRY CULTIVARS IN THE ISSYK-KUL REGION OF KYRGYZSTAN - G. E. Sariyeva; M. K. Turdieva; Zh. T. Aitbaeva; S. K. Kadyrkulova; Sh. K. Kachekova; A. K. Kudaibergenova (Овощи России, 2019)
The Issyk-Kul region is one of the most preferable for horticulture regions of Kyrgyzstan. However, during last decades the biological and agronomical diversity in this region is significantly decreasing due to transmission to market economics. In this term the aim of our survey was estimating of present level of diversity of fruit trees and wild berries, as well as vitamin content after long winter storage. This survey was organized in two districts of Issyk-Kul region – Dzhety-Oguz and Ak-Suu by the interview of 217 local farmers, the vitamin content was determined by known methodic. The study showed that there are 4 varieties of pears, of which 3 are local / traditional; 8 varieties of apricot with 5 local and 26 varieties of apple with 21 local. More than half of the local varieties of pears, apples and apricots disappear at the present time due to different reasons (non-compliance with market requirements for long-distance storage and transportation of fruits, bacterial burn disease that affected 90% of all pear plantations, lack of planting material and of knowledge and skills for grafting, treatment for diseases without antibiotics, agrotechniques) and are actively replaced by new commercial varieties. Among 8 varieties of apple and pear there were no varietal differences in the content of vitamins, but all of cultivars were significantly inferior to wild berry shrubs - viburnum, barberry, and dog rose for the content of vitamins A, C, B3, β-carotene. Based on the results of the survey, were developed practical recommendations for farmers on preserving the diversity of local varieties of fruit trees and wild berry shrub.